A novel AIE chemosensor based on a coumarin functionalized pillar[5]arene for multi-analyte detection and application in logic gates. (17th June 2020) - Dong, Hong-Qiang; Ma, Xiao-Qiang; Wei, Tai-Bao; Yang, Qing-Yu; Zhang, Yun-Fei; Zhang, Qin-Peng; Yao, Hong; Zhang, You-Ming; Lin, Qi
Abstract : A novel coumarin functionalized pillar[5]arene (PX ) with AIE fluorescence could sequentially detect multiple analytes in aqueous medium with high sensitivity. Abstract : Aggregation induced emission (AIE) active molecules are widely applied for multi-analyte detection due to their unique advantages over conventional fluorescent probes. Herein, a novel coumarin functionalized pillar[5]arene (PX ) has been designed and synthesized. It has strong AIE activity, and the fluorescence quantum yield of PX turned out to be 35.0% in DMF/H2 O (7 : 3, v/v) binary solution (1.0 × 10 −4 M). Meanwhile, the optimized structure of PX was obtained by theoretical calculation at the B3LYP/6-311G level. Interestingly, the PX displays high sensitivity to multiple analytes, such as Fe 3+ and Ba 2+ . The limits of detection (LODs) of PX for Fe 3+ and Ba 2+ are 1.67 × 10 −7 M and 5.89 × 10 −8 M, respectively. In addition, by introducing metal ions into the AIE chemosensor of PX, a metal-coordinated chemosensor (PX–M ) was obtained. The PX–Fe and PX–Ba show selective fluorescence "turn on" detection of H2 PO4 − (LOD = 1.50 × 10 −7 M) and CN − (LOD = 6.20 × 10 −7 M), respectively. The multi-analyte detection mechanism of PX was based on multiple competitions of "exo-wall π–π" interactions and cation–π interactions. Notably, we have prepared logic gates controlled by Fe 3+ /Ba 2+ and H2 PO4 − /CN − at the molecular level, which can quickly and efficiently detect ions in aqueous solutions. Moreover, we also prepared test films, and an Fe 3+ test kit was prepared by loading PX on a silica gel plate. This study provides a new way for multi-analyte detection.